Prediction of Pediatric Mortality in Bahrami Children's Hospital Pediatric Intensive Care Unit (PICU) based on Pediatric Index of Mortality-2 (PIM2) - Payman Salamati; Mousa Zargar; Asgar Eghbalkhah; Reza Chaman; Kambiz Sotoudeh; Behdad Navabi; Zahra Mokhtari (مجله دانشکده پزشکی اصفهان, 2010)
Background: This study assessed to study Pediatric Index of Mortality-2 (PIM2) measure for outcome assess-ment of children admitted to pediatric intensive care unit (PICU) of Bahrami children’s hospital.